Antibiotic prescription after tooth extraction in adults: a retrospective cohort study in Austria - Safoura Sheikh Rezaei; Brigitte Litschauer; Karolina Anderle; Stephanie Maurer; Patrick Jan Beyers; Berthold Reichardt; Michael Wolzt (BMC, 2022)
Abstract Background Broad spectrum antibiotics are often used for the prophylaxis of infectious endocarditis and treatment of odontogenic infections, but there are limited data related to antibiotic use and adherence to prescription guidelines.  Methods Data from patients with tooth extraction between 2014 and 2018 were selected from a database of a regional health insurance fund. We created three data sets, one based on all tooth extractions, one on multiple teeth extractions, and one including only single tooth extraction. After data collection, descriptive analysis was carried out. The differences in prescription pattern of antibiotic medicine were tested by χ2 test, Student´s t-test or ANOVA. Results From 43,863 patients with tooth extraction, 53% were female, and 3,983 patients (9.1%) filled a prescription for antibiotic medicine. From 43,863 patients, 157 patients (0.4%) had endocarditis risk, but only 8 patients of these (5.1%) filled an antibiotic prescription. In total, 9,234 patients had multiple and 34,437 patients had only one tooth extraction. Patients with more than one tooth extraction received more often antibiotic treatment (10.7%) compared to those with single tooth extractions (χ2 = 36; p < 0,001). Patients with more than one tooth extraction were older, however, younger patients received antibiotics more frequently (t = 28,774, p = 0.001). There was no relationship with endocarditis risk status. Clindamycin and amoxicillin/clavulanic acid were the most frequently prescribed antibiotic medicines. Conclusions In this retrospective cohort study, dentists did not discriminate prophylactic antibiotic prescription with regard to endocarditis risk status. A factor influencing prescribing behaviour of antibiotic medicines was the number of extracted teeth.